Analisis Persepsi dan Preferensi Masyarakat Disabilitas terhadap Kebijakan dan Fasilitas Disabilitas di Kota Pekanbaru Riau - Jeni Wardi; Anto Ariyanto; Latifa Siswati; David Setiawan; Guntoro Guntoro; Lisnawita Lisnawita*; Olivia Anggie Johar; Widya Apriani; Nurhamin Nurhamin; Fenty Widya; Ririn Sari Wati; Rizky Octa Putri Charin; Budia Misri (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2023)
The low accessibility of handling and services for persons with disabilities in Pekanbaru City, Riau Province, will certainly be an obstacle to the fulfillment and protection of rights for persons with disabilities. These barriers will have an impact on the development and rights of life for these marginalized people. Therefore, it is necessary to conduct an assessment to map the general situation and optimize the fulfillment of the rights of persons with disabilities. In this case, the researcher appointed Pekanbaru City as the focus of research. The stages of the research method are literature study, interviews, field observations, focus group discussions and data analysis. The results of this study will be used as a basis for developing policies that are inclusive of persons with disabilities so that they have equal opportunities before the State to enjoy social, economic, political, civil and cultural rights. The purpose of the study was to analyze the perception of the disabled community towards disability policies and facilities in the city of Pekanbaru and to analyze the preferences of the disabled community towards policies and facilities. The results show that the highest need for Infrastructure is 93%. In the Health sector, Hospital Needs with a percentage of 95.4%, Business Capital Requirements really help the economy of families with disabilities, namely the largest response of 94.70%, the Education Sector for special knowledge needs for disabilities the largest 84.3%, and the religious field needs lecturers and preachers disability-friendly 78.9%.